Same-Day Discharge After Minimally Invasive Myomectomy. Issue 3 (March 2016) - Alton, Katie; Sullivan, Shannon; Udaltsova, Natalia; Yamamoto, Miya; Zaritsky, Eve
Abstract : OBJECTIVE: To estimate readmission rates of patients discharged home the same day after a minimally invasive myomectomy. METHODS: This is a retrospective case series of patients who underwent minimally invasive myomectomy and were discharged the same day, which examines the feasibility and safety by rates of readmission within Kaiser Permanente Northern California. Chart review was performed for outcomes of interest including readmission rates, emergency department, and urgent clinic visits within 48 hours, 7 days, and up to 3 months along with surgical and demographic characteristics. RESULTS: Of the 403 minimally invasive myomectomies performed during the study period, 88% (N=356) of patients were discharged home the same day. No readmissions required reoperation or were life-threatening. Two patients (0.6%) were readmitted within 48 hours for postoperative fever. A cumulative total of five patients (1.4%) were readmitted within 3 months. Urgent care and emergency department visits occurred in zero and seven patients (2.0%) within 48 hours of discharge, most commonly for pain and urinary retention. Median leiomyoma weight was 204 g, median body mass index was 26, median blood loss was 75 mL, and median surgical time was 157 minutes. CONCLUSION: Same-day discharge after minimally invasive myomectomy was found to have a low readmission rate and low health care utilization in the immediate postoperative period. Same-day discharge appears to be a safe option for healthy patients after undergoing an uncomplicated minimally invasive myomectomy. Abstract : Same-day discharge is a safe option for healthy patients undergoing an uncomplicated laparoscopic or robotic myomectomy.